L. johnsonii, L. plantarum, and L. rhamnosus alleviated Enterohaemorrhagic Escherichia coli-induced diarrhoea in mice by regulating gut microbiota. (May 2021) - Hu, Yafan; Zhao, Mengna; Lu, Zhaoxin; Lv, Fengxia; Zhao, Haizhen; Bie, Xiaomei
Abstract: Enterohaemorrhagic Escherichia coli (EHEC) is a prominent foodborne pathogen that causes infectious intestinal diarrhoea. Lactobacillus is a recognized probiotic that inhibits intestinal pathogens and maintains the balance of the intestinal flora. The purpose of this study was to investigate the regulatory effects of three Lactobacillus strains, L. johnsonii, L . plantarum, and L. rhamnosus, on the intestinal flora of EHEC-infected mice. The initial weight and diarrhoea index of the mice were recorded. After 21 days, the faeces of the mice were subjected to 16S rDNA high-throughput sequencing. The diarrhoea index of mice treated with Lactobacillus improved, their body weight continued to rise, and their liver index gradually decreased. The α diversity analysis showed that the intestinal flora diversity and abundance were lower in mice infected with EHEC than in healthy mice. L. plantarum, L. johnsonii, and L. rhamnosus significantly improved the diversity of the flora species. In terms of flora composition, the three main phyla present were Bacteroidetes, Firmicutes, and Proteobacteria. The abundance of these three phyla was reduced to 93.81% after infection and restored to over 96.30% after treatment. At the genus level, Lactobacillus reduced the abundance of Bacteroides, Helicobacter pylori, and Shigella, while increasing the abundance of butyric acid-producing bacteria and Lactobacillus . Finally, a heat map and non-metric multidimensional scaling analysis showed that the intestinal flora structures in the L. johnsonii, L. plantarum, and L. rhamnosus treatment groups were closest to those of healthy mice. In conclusion, L. johnsonii, L. plantarum, and L. rhamnosus regulated and improved the structure of intestinal flora and relieved diarrhoea caused by EHEC infection. Highlights: Symptoms of E. coli-infected mice treated with Lactobacillus improved. L. plantarum, L. johnsonii, and L. rhamnosus improved gut flora diversity. Lactobacillus was effective in restoring gut flora.